PENGARUH STORE IMAGE TERHADAP PERSEPSI KUALITAS PRIVATE LABEL CARREFOUR PALING MURAH DI CARREFOUR GOLDEN CITY MALL SURABAYA - Inge Yunita Pramestya, ; Widyastuti, (Bisnis dan Manajemen, 2010)
Today the world has witness the birth of many retailers, it also making more and more private label are available that issues by the retailer itself. Because of that, the private label as the brand owned by a retailer is always connected to the Store Image of that retailer. In order to increase the quality of the private label, therefore the shop has to focus to increase the image from its store. The Store Image is depicted as the complex consumers perceptions from the different attributes or distinctive from a store. The Store Image itself is consisted of Service, Convenience, Quality, Selection/Variety, Price and Atmosphere. This research will be focuses on the influence of the store image against the quality of Carrefour private label Paling Murah by the customers at Golden City Mall Carrefour Surabaya. The type of this research is a conclusive study uses causal research. The population of this study were men and women at least 17 years of age. The sample in this study are the customers of Golden City Mall Carrefour Surabaya that knowing Carrefour private label Paling Murah as many as 115 respondents. Non probability sampling technique using Purposive sampling way is used to determine the sample of this research. The data of this research analized by multiple linier regression analysis. The result of this research shows coefficient of determination 0,68, it means that there is an influence variable independent to dependent variable equal to 68% and the rest of 32% influenced by other variables outside this research. The most dominant variable in this research is brand awareness variable by t value of 6,109.